Moderate concentrations of ethanol inhibit endocytosis of the yeast maltose transporter. - Lucero, P (1997)
The maltose transporter in Saccharomyces cerevisiae is degraded in the vacuole after internalization by endocytosis upon nitrogen starvation in the presence of a fermentable substrate. This degradation, known as catabolite inactivation, is inhibited by the presence of moderate concentrations (2 to 6%, vol/vol) of ethanol. We have investigated the mechanism of this inactivation and have found that it is due to the inhibition of the internalization of the transporter by endocytosis. The results also indicate that this inhibition is due to alterations produced by ethanol in the organization of the plasma membrane which also affects to endocytosis of other plasma membrane proteins. Apparently, endocytosis is particularly sensitive to these alterations compared with other processes occurring at the plasma membrane.